Twice dead : - Lock, Margaret (University of California Press, 2002)
Twice Dead is a marvel of perfect tensions. While eschewing simple cultural dichotomies, it deftly balances the immediacy of interviews with deep historical reflection; its theoretical insights are razor-sharp, yet its spirit is unfailingly compassionate. Wise and eminently readable, Lock's superb book portrays how impersonal, modern technology compels us to grapple with the most intimate, age-old questions-the bonds between bodies and persons, the borders between the living and the dead